Association between knowledge and depression at rising time of COVID-19 in Bangladesh - Sharmin Akhtar; Rubel Ahmed; Arnaba Saha Chaity; Mutasim Billah (Intelektual Pustaka Media Utama, 2021)
Novel coronavirus (nCoV) has created a new challenging situation all over the world. In Bangladesh, people are facing some difficulties to response the emergencies. There are so many people who are lacking of proper quarantine information and knowledge about prevention practices towards coronavirus disease 2019 (COVID-19). COVID-19 has created an experience of mental disorder like depression, anxiety, and stress. Although social media, newspaper, news, television has focused on this issue, still there is to be needed to identify the psychological effects like negative impact on our mind and behavioral changes during lockdown. An online survey of 248 respondents was conducted between April, 15 2020 and May, 15 2020. The aim of this study was to assess the relationship between higher knowledge of public regarding safety measures and depression among the adult population of Bangladesh during lockdown. This study focused on correlation between knowledge level and mental health condition like depression. About 50% respondents were felt high depression after the first announcement of lockdown in Bangladesh. Approximately 50% respondents stated that people of their locality were panicked, not panicked were 26.21% and the probability of getting panic were 23.79% due to COVID-19 during lockdown in Bangladesh. The respondents who had gathered a higher knowledge about precautions were associated with depression.